Synchronization of HeLa cell cultures by inhibition of DNA polymerase alpha with aphidicolin. - Pedrali-Noy, G (1980)
Both the inhibitory effect of aphidicolin on the replicative alpha-polymerase and the reversibility of its action in vivo (Pedrali-Noy & Spadari, 1979, Biochem. Biophys. Res. Commun. 88, 1194-2002) allow the synchronization of cells in culture. Aphidicolin prevents G1 cells from entering the DNA synthetic period, blocks cells in "S" phase, allows G2, M and G1 cells to continue the cell cycle and to accumulate at the G1/S border. Aphidicolin is a more useful reagent than hydroxyurea and thymidine because it does not affect cell viability or "S" phase duration and does not interfere with the synthesis of dNTPs or DNA polymerases. In fact cells exposed to the drug continue to synthesize all three DNA polymerases alpha, beta and gamma as well as all dNTPs which, when the block is removed, are present at levels optimal for DNA initiation and replication. The technique is simple and can be applied to cells growing in suspension or monolayers and allows one to harvest large quantities of synchronized cells.